2018
DOI: 10.1002/fsn3.780
|View full text |Cite
|
Sign up to set email alerts
|

Association of raisin and raisin‐containing food consumption with nutrient intake and diet quality in US children: NHANES 2001‐2012

Abstract: BackgroundRaisins are a commonly consumed dried fruit and given their nutrient profile may offer nutritional and health benefits.ObjectiveTo examine the association between consumption of raisins and raisin‐containing foods with nutrient intake and dietary quality in children.MethodsNational Health and Nutrition Examination Survey (NHANES) data for 2001–2012 in those 2–18 years of age (n = 20,175) were used. Consumers of raisins (n = 154, 51.6% female) and raisin‐containing foods (n = 1,993, 52.5% female) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…NHANES, as a large-scale epidemiological survey, provides a unique platform for examining the impact of diet quality on the general population. Leveraging NHANES data, numerous studies have assessed the association between the consumption of common foods, such as cereal, yogurt, orange juice, and raisins, and diet quality (assessed by HEI-2015 score) in US children [ 23 , 24 , 25 , 26 ]. Jun et al studied the relationship between food insecurity and diet quality in US children through NHANES 2011–2016 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…NHANES, as a large-scale epidemiological survey, provides a unique platform for examining the impact of diet quality on the general population. Leveraging NHANES data, numerous studies have assessed the association between the consumption of common foods, such as cereal, yogurt, orange juice, and raisins, and diet quality (assessed by HEI-2015 score) in US children [ 23 , 24 , 25 , 26 ]. Jun et al studied the relationship between food insecurity and diet quality in US children through NHANES 2011–2016 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later, Fulgoni et al [76] examined the association between the ingestion of raisins and raisin-containing foods with nutrient intake and dietary quality in children and adolescents 2-18 years of age. The study found that raisin consumers had significantly higher daily intakes of dietary fiber (22.9%), potassium (16%) and magnesium (11.6%), and lower intakes of added sugar (−19.1%), monounsaturated fat (−9.2%) and total fat (−5.1%) compared to non-consumers.…”
Section: Diet Qualitymentioning
confidence: 99%
“…Raisin is a kind of nutritious and diverse agricultural product, which is rich in nutrients such as sodium, iron, calcium, and dietary fiber 1 . Studies have found that eating raisins three times a day can significantly reduce blood sugar levels, systolic and diastolic blood pressure, thereby reducing the risk of diabetes and cardiovascular and cerebrovascular diseases in consumers 2 . Furthermore, compared with carbohydrate foods with the same calorie, raisins can effectively reduce cholesterol levels and have anti-inflammatory and anti-cancer effects.…”
Section: Introductionmentioning
confidence: 99%